Repetition Preferences in Two-Handed Balanced Signs: Vestigial Locomotor Central Pattern Generators Shape Sign Language Phonetics and Phonology - Tkachman, Oksana; Purnomo, Gracellia; Gick, Bryan (Frontiers in Communication, 2021)
Language is produced by bodies that evolved to fulfill a variety of functions, most of them non-communicative. Vestigial influences of adaptation for quadrupedal locomotion are still affecting bimanual actions, and have consequences on manual communication systems such as sign languages of the deaf. We discuss how central pattern generators (CPGs), networks of nerve cells in the spinal cord that drive locomotion, influence bimanual actions with alternating movements to be produced with repeated motion. We demonstrate this influence with data from three unrelated sign languages, American Sign Language, British Sign Language, and Hong Kong Sign Language: in all three sign languages two-handed balanced signs produced with alternating movements have a tendency to be repeated, whereas other types of two-handed balanced signs show the opposite tendency for single movements. These tendencies cannot be fully explained by factors such as iconicity. We propose a motoric account for these results: as alternating bimanual movements are influenced by locomotor patterns, they favor repeated movements.